Comparison of the effect of benzathine penicillin G, clarithromycin, cefprozil and amoxicillin/clavulanate on the bacteriological response and throat flora in group A beta hemolytic streptococcal tonsillopharyngitis - Yildirim, Inci; Ceyhan, Mehmet; Gür, Deniz; Kaymakoğlu, Ibrahim (The Turkish Journal of Pediatrics, 2008)
Bacteriological failure with penicillin that has been used widely for years in group A beta hemolytic streptococcal (GABHS) tonsillopharyngitis is being reported as high as 30%. Because of this unresponsiveness, many different agents are being used as alternative options. We evaluated the effect of clarithromycin, amoxicillin/clavulanate (CAM), cefprozil and benzathine penicillin G (Pen G) on the bacteriological cure, beta-lactamase production, pharyngeal microflora and alpha hemolytic streptococci (AHS) when used in the treatment of pediatric GABHS tonsillopharyngitis. Intramuscular Pen G and oral clarithromycin, CAM and cefprozil were administered to 70 patients who were between 2-16 years of age. Three throat swabs were obtained from each patient (before treatment, and 3 days and one month after treatment). The cultures were evaluated for aerobic and anaerobic bacteria, beta lactamase production, AHS and fungi isolation. Bacteriological cure rates were similar in the four treatment groups (p>0.05). Isolation rates of AHS were 97.1% and 77.9% in clarithromycin group, 100% and 83.8% in CAM group, 97.2% and 98.6% in cefprozil group and 100% and 83.8% in the Pen G group before and after treatment, respectively. The most prominent inhibitory effect on AHS was observed with CAM, while cefprozil had the least effect (p